(7x-6)/3=6

Simple and best practice solution for (7x-6)/3=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x-6)/3=6 equation:



(7x-6)/3=6
We move all terms to the left:
(7x-6)/3-(6)=0
We multiply all the terms by the denominator
(7x-6)-6*3=0
We add all the numbers together, and all the variables
(7x-6)-18=0
We get rid of parentheses
7x-6-18=0
We add all the numbers together, and all the variables
7x-24=0
We move all terms containing x to the left, all other terms to the right
7x=24
x=24/7
x=3+3/7

See similar equations:

| 3x(x-5)-3x²=30 | | 4/2=n | | (12-3y)/6=(y-4)/2 | | 3/n=5 | | 3x-12=5x-28 | | 100x/2=60x-2 | | 32=4x+14 | | 20x/6-4x/3=2 | | 2x+10/4=8x-5/6 | | -u+184=54 | | -16+5x=4(3x=+7x) | | p²-6p+5=0 | | 203=-y+127 | | 0.5w=-35 | | 25÷3x-8÷5=9÷4 | | (25/3)x-8/5=9/4 | | x/6-x/12+5=x+5 | | 25/3(x)-8/5=9/4 | | 25/3x-8/5=9/4 | | .01(x+5)-0.05=0.01(6x+5) | | 1/2x-2=-3+2 | | 12x-4x+14=2x | | 227=-y+2 | | 227=-y | | 252-y=109 | | y/5-12=30 | | -3x*(-3x)+6x=-1 | | 5x-8=-4+9 | | 3x+6=6x+8 | | 14(8x-4)=7x-6 | | 9=6+x7 | | 262,5=x/8 |

Equations solver categories